Anandamide Protects HT22 Cells Exposed to Hydrogen Peroxide by Inhibiting CB1 Receptor-Mediated Type 2 NADPH Oxidase. (17th July 2014) - Jia, Ji; Ma, Lei; Wu, Mingchun; Zhang, Lei; Zhang, Xiajing; Zhai, Qian; Jiang, Tao; Wang, Qiang; Xiong, Lize
Abstract : Background. Endogenous cannabinoid anandamide (AEA) protects neurons from oxidative injury in rodent models; however the mechanism of AEA-induced neuroprotection remains to be determined. Activation of neuronal NADPH oxidase 2 (Nox2) contributes to oxidative damage of the brain, and inhibition of Nox2 can attenuate cerebral oxidative stress. We aimed to determine whether the neuronal Nox2 was involved in protection mediated by AEA. Methods. The mouse hippocampal neuron cell line HT22 was exposed to hydrogen peroxide (H2 O2 ) to mimic oxidative injury of neurons. The protective effect of AEA was assessed by measuring cell metabolic activity, apoptosis, lactate dehydrogenase (LDH) release, cellular morphology, intracellular reactive oxygen species (ROS), and antioxidant and oxidant levels and Nox2 expression. Results. HT22 cells exposed to H2 O2 demonstrated morphological changes, decreased LDH release, reduced metabolic activity, increased levels of intracellular ROS and oxidized glutathione (GSSG), reduced levels of superoxide dismutase (SOD), and reduced glutathione (GSH) and increased expression of Nox2. AEA prevented these effects, a property abolished by simultaneous administration of CB1 antagonist AM251 or CB1-siRNA. Conclusion. Nox2 inhibition is involved in AEA-induced cytoprotection against oxidative stress through CB1 activation in HT22 cells.